S-alkylated homocysteine derivatives: new inhibitors of human betaine-homocysteine S-methyltransferase - Jiracek, Jiri; Collinsova, Michaela; Rosenberg, Ivan; Budesinsky, Milos; Protivinska, Eva; Netusilova, Hana; Garrow, Timothy A (Journal of medicinal chemistry, 2006)
A series of S-alkylated derivatives of homocysteine were synthesized and characterized as inhibitors of human recombinant betaine-homocysteine S-methyltransferase (BHMT). Some of these compounds inhibit BHMT with IC50 values in the nanomolar range. BHMT is very sensitive to the structure of substituents on the sulfur atom of homocysteine. The S-carboxybutyl and S-carboxypentyl derivatives make the most potent inhibitors, and an additional sulfur atom in the alkyl chain is well tolerated. The respective (R,S)-5-(3-amino-3-carboxy-propylsulfanyl)-pentanoic, (R,S)-6-(3-amino-3-carboxy-propylsulfanyl)-hexanoic, and (R,S)-2-amino-4-(2-carboxymethylsulfanyl-ethylsulfanyl)-butyric acids are very potent inhibitors and are the strongest ever reported. We determined that (R,S)-5-(3-amino-3-carboxy-propylsulfanyl)-pentanoic acid displays competitive inhibition with respect to betaine binding with a Kappi of 12 nM. Some of these compounds are currently being tested in mice to study the influence of BHMT on the metabolism of sulfur amino acids in vivo.
Keywords: Pentanoic Acids; sulfidy; Stereoisomerism; kyseliny pentanové; Structure-Activity Relationship; Sulfides; lidé; Caproates; stereoizomerie; vztahy mezi strukturou a aktivitou; Humans; Betaine-Homocysteine S-Methyltransferase; betain-homocystein-S-methyltransferasa; butyráty; Butyrates; kapronáty; homocystein; Homocysteine